2020
DOI: 10.1016/j.injury.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 has affected emergent visits to a Latin-American trauma department: Experience at a Peruvian national trauma referral center

Abstract: Highlights As in other countries Health problems such as osteoporotic hip fractures may in fact remain stable during the implementation of stringent lock-down measures for the population. Like osteoporotic hip fractures, diabetic foot ulcers are usually manifested in elderly, non-working people, whose risk of injury thereby should not have been impacted by staying home from work. In our study, the four most common indications for our surgery service admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 18 publications
6
30
1
1
Order By: Relevance
“…The time window evaluated by the authors on head trauma was between March 23 and April 22, 2021, a period in which a large part of the sample evaluated was expected to be under strict confinement, where clearly mobility on the streets was null, and consequently, the accident rate would also be considerably reduced. These results are compatible with studies that evaluated patients on similar dates [3] , [4] . When analyzing the time window of the study by Prawiroharjo et al [5] , who followed up until June, they observed an increase in the incidence of traumatic brain injury (157/752 (20.9%) vs 106/766 (13.8%), p < 0.001), with respect to the previous year [5] .…”
supporting
confidence: 91%
“…The time window evaluated by the authors on head trauma was between March 23 and April 22, 2021, a period in which a large part of the sample evaluated was expected to be under strict confinement, where clearly mobility on the streets was null, and consequently, the accident rate would also be considerably reduced. These results are compatible with studies that evaluated patients on similar dates [3] , [4] . When analyzing the time window of the study by Prawiroharjo et al [5] , who followed up until June, they observed an increase in the incidence of traumatic brain injury (157/752 (20.9%) vs 106/766 (13.8%), p < 0.001), with respect to the previous year [5] .…”
supporting
confidence: 91%
“…Even when all patients tested negative for SARS-CoV-2 virus infection, patients treated during the pandemic were frailer and less mobile, resulting in a higher mortality rate. Pintado et al 27 reported a significant decrease in most emergency department visits except for osteoporotic fractures in a Peruvian trauma center. To our knowledge, this is the only report to date to specifically address mortality in hip fracture patients with a concomitant SARS-CoV-2 infection in a Latin-American country, with comparable results to case series from other locations.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, the proportion of children older than 10 years presenting with trauma declined by 35% during the same period. Decreases in injury-related ED visits have been reported in Latin America, 32 , 35 Spain, 20 , 35 Ireland, 36 United States, 8 and United Kingdom 12 and were attributed to reductions in traffic crashes, workplace accidents, and extracurricular activities. We postulate that the increase in trauma-related ED visits in our younger study population may be related to accidents in the home environment, such as falls and burns, 37 in contrast to the aforementioned injuries, which are more typical in teenagers.…”
Section: Discussionmentioning
confidence: 99%